Reversibly Immortalized Mouse Articular Chondrocytes Acquire Long-Term Proliferative Capability While Retaining Chondrogenic Phenotype. Issue 6 (June 2015) - Lamplot, Joseph D.; Liu, Bo; Yin, Liangjun; Zhang, Wenwen; Wang, Zhongliang; Luther, Gaurav; Wagner, Eric; Li, Ruidong; Nan, Guoxin; Shui, Wei; Yan, Zhengjian; Rames, Richard; et al.
Cartilage tissue engineering holds great promise for treating cartilaginous pathologies including degenerative disorders and traumatic injuries. Effective cartilage regeneration requires an optimal combination of biomaterial scaffolds, chondrogenic seed cells, and biofactors. Obtaining sufficient chondrocytes remains a major challenge due to the limited proliferative capability of primary chondrocytes. Here we investigate if reversibly immortalized mouse articular chondrocytes (iMACs) acquire long-term proliferative capability while retaining the chondrogenic phenotype. Primary mouse articular chondrocytes (MACs) can be efficiently immortalized with a retroviral vector-expressing SV40 large T antigen flanked with Cre/loxP sites. iMACs exhibit long-term proliferation in culture, although the immortalization phenotype can be reversed by Cre recombinase. iMACs express the chondrocyte markers Col2a1 and aggrecan and produce chondroid matrix in micromass culture. iMACs form subcutaneous cartilaginous masses in athymic mice. Histologic analysis and chondroid matrix staining demonstrate that iMACs can survive, proliferate, and produce chondroid matrix. The chondrogenic growth factor BMP2 promotes iMACs to produce more mature chondroid matrix resembling mature articular cartilage. Taken together, our results demonstrate that iMACs acquire long-term proliferative capability without losing the intrinsic chondrogenic features of MACs. Thus, iMACs provide a valuable cellular platform to optimize biomaterial scaffolds for cartilage regeneration, to identify biofactors that promote the proliferation and differentiation of chondrogenic progenitors, and to elucidate the molecular mechanisms underlying chondrogenesis.